IMPACT OF ADVANCED AND DELAYED IRRIGATION PRACTICES ON PHYSICO-CHEMICAL ATTRIBUTES OF POTATO TUBERS UNDER BED SOWING - M. S. Waqas; M. J. M. Cheema; S. Hussain; A. Daccache; M. K. Ullah; M. M. Iqbal; H. Hussain (Journal of Animal and Plant Sciences, 2022)
The wise use of water resources is the dire need of the day due to the alarming situation of water crisis. Management Allowed Depletion (MAD) level irrigation technique is used to enhance crop yield as well as the precise use of water. The present study was designed to investigate the optimum MAD level (when to irrigate) at which tuber yield and quality did not deteriorate significantly. Four different MAD levels were scheduled i.e., irrigation applied when MAD0 = 0%, MAD20 = 20%, MAD35 = 35%, and MAD50 = 50% of available soil water depleted from the soil at Water Management Research Center, University of Agriculture, Faisalabad-Pakistan during the two successive winter growing seasons (2014-15 and 2015-16). Data of different physico-chemical properties and yield of potato tubers were gathered under the Randomized Complete Block Design (RCBD) and set into standard statistical techniques. Results revealed that physical parameters (i.e., length, thickness, diameter, weight, and actual volume) of potato tubers were significantly affected by the different MAD levels, while MAD35 was at par with other irrigation schedules. Different MAD levels didn’t show significant effects on some of the physico-chemical properties (i.e., particle density, porosity, specific gravity, tuber starch content, and total soluble solids) of potato tubers, and revealed that these traits are entirely genetic based. While tuber size percentage and yield are significantly affected by the different MAD levels. The maximum yield (i.e., 15.52, 16.76 in tons acre-1) and crop water productivity (i.e., 14.19 and 14.64 in kg m-3) were also observed at MAD35 during both years. In nutshell, results revealed that both advanced and delayed irrigation practices severely affect the physical parameters, yield as well as to some extent physico-chemical traits of potato tubers. Therefore, 35% MAD level schedule is the optimum one and recommended for potato cultivation under bed sowing.
Keywords: Drip irrigation; Management allowed depletion; Horticultural crops; Irrigation scheduling; Starch content; Specific gravity